Quadrivalent meningococcal conjugate vaccines. - Pace, D; Pollard, A; Messonier, N (2009)
Neisseria meningitidis is an important cause of bacterial meningitis and septicaemia with most disease caused by meningococci bearing serogroups A, B, C, Y and W-135 polysaccharides. Monovalent serogroup C conjugate vaccines have become established in the immunisation programmes in many countries and the first quadrivalent meningococcal vaccine, containing the polysaccharides from 4 of the serogroups A, C, Y and W-135 meningococci conjugated to a protein carrier was licensed in the US in 2005. This vaccine and others in development offer the potential to broaden population protection against meningococcal disease.